Distressed Stocks in Distressed Times - Eisdorfer, Assaf; Misirli, Efdal Ulas (Management Science, 2020)
We partially explain the well-documented distress anomaly by studying the risk/return relation of distressed stocks across market states. We show that the anomaly does not hold in market downturns. The asset beta and financial leverage of distressed stocks rise significantly during bear markets, resulting in a dramatic increase in their equity beta. Hence, a long/short healthy-minus-distressed trading strategy leads to significant losses when the market rebounds. Managing this risk mitigates the severe losses of financial distress strategies and significantly improves their Sharpe ratios. Our results remain strongly significant controlling for the momentum effect and are robust to various estimation procedures. This paper was accepted by Tyler Shumway, finance.